Market territories and urban centralities: a comparative analysis of public food markets in São Paulo (Brazil) and Santiago (Chile) - Bitelli, Fábio Molinari; Suzuki, Júlio César (Geografares, 2026)
This article analyzes, from a comparative perspective, the public markets of São Paulo (Brazil) and Santiago (Chile) as mercantile territories and resilient urban centralities in Latin America. Based on a historical-cultural and territorial approach (period from 1850 to 2021), supported by qualitative research using documentary analysis, field observation, and spatial mapping, it investigates how these spaces articulate traditional trade practices, circulation networks, power relations, and local identities. The results show that public markets are spaces of social production of territory, mediating tensions between tradition and modernity, public and private, local and global. The analysis reinforces their role as social institutions that resist contemporary urban transformations, contribute to the consolidation of local food supply networks, and structure urban centralities in their surroundings.